Pengaruh Pemahaman Peraturan Perpajakan, Kesadaran Wajib Pajak, Akuntabilitas Pelayanan Publik Dan Kewajiban Moral Terhadap Kepatuhan Wajib Pajak (Studi Empiris pada Kantor Bersama SAMSAT Kota Jambi) - ruky, nuraini elfa; Putra, Wirmie Eka; Mansur, Fitrini (Program Studi Akuntansi FPEB UPI, 2018)
This study aims to obtain empirical evidence of the influence of understanding tax regulations, awareness of taxpayers, accountability of public services and moral obligations towards taxpayer compliance. The population in this study were all motor vehicle taxpayers registered at the SAMSAT Office in Jambi City. The sampling technique in this study used the accidental sampling method. The data analysis technique uses multiple linear regression analysis techniques. The number of samples in this study were 100 respondents of motor vehicle taxpayers. The software used for data processing is SPSS version 22 for Windows. The results of testing the hypothesis are as follows. Simultaneously and partially, understanding tax regulations, taxpayer awareness, public service accountability and moral obligations towards taxpayer compliance.